Gambaran Indeks Eritrosit Rerata pada Laki-laki Dewasa dengan Diabetes Melitus Tipe 2 - Saraswati, Talitha D.; Rotty, Linda W. A.; Pandelaki, Karel (e-CliniC, 2019)
Abstract: Diabetes mellitus (DM) is a metabolic disease indicated by high level of blood sugar resulting from a defect in insulin secretion, insulin activity, or both. The prevalence of DM in Indonesia is 1.9%, making it the 7th leading cause of deaths worldwide. In diabetic patients it is common to find any disorder in several systems, inter alia disorder of erythrocytes. An important indicator in portraying the erythrocytes state is the average erythrocyte indices (MCV, MCH, and MCHC). This study was aimed to provide an overview of the average erythrocyte indices in young adult males with type 2 DM (T2DM) at the Endocrine Polyclinic of Prof. Dr. R. D. Kandou Hospital. This was a descriptive and retrospective study using medical records of diabetic patients at the Endocrine Policlinic from September 2018 to September 2019. The results obtained a total of 1.432 medical records consisting of 550 males and 882 females. However, only 22 samples met the inclusion criteria, with a majority of samples were 40 to 45 years old (50%). Generally, the erythrocyte indices were still in normal range. Albeit, a few samples showed a decrease in hemoglobin level, MCV, and MCH. In conclusion, there was no significant change in the erythrocyte indices among adult males with type 2 diabetes mellitus at the Endocrine Polyclinic of Prof. Dr. R. D. Kandou Hospital.Keywords: average erythrocyte indices, type 2 diabetes mellitusÂ Abstrak: Diabetes melitus (DM) merupakan penyakit metabolik yang ditandai dengan tingginya kadar gula darah akibat defek sekresi insulin, kerja insulin, atau keduanya. Prevalensi DM di Indonesia sebesar 1,9% menjadikan DM sebagai penyebab kematian urutan ke tujuh di dunia. Pada pasien DM seringkali ditemukan gangguan pada berbagai sistem, salah satunya pada eritrosit. Indikator penting yang dapat mencerminkan keadaan eritrosit ialah indeks eritrosit rerata (MCV, MCH, dan MCHC). Penelitian ini bertujuan untuk mengetahui gambaran indeks eritrosit rerata pada pasien laki-laki dewasa penyandang DM tipe 2 di Poliklinik Endokrin RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medik pasien di Poli Endokrin RSUP Prof. Dr. R. D. Kandou periode September 2018 hingga September 2019. Hasil penelitian mendapatkan 1.432 rekam medis, terdiri dari 550 laki-laki dan 882 perempuan, namun hanya 22 data yang memenuhi kriteria penelitian, dengan mayoritas berusia 40-45 tahun (50%). Secara umum nilai indeks eritrosit rerata masih dalam rentang normal, namun terdapat beberapa sampel dengan penurunan kadar hemoglobin, MCV, dan MCH. Simpulan penelitian ini ialah tidak terdapat gambaran bermakna pada indeks eritosit pasien laki-laki dewasa dengan DM tipe 2 di Poliklinik Endokrin RSUP Prof. Dr. R. D. KandouKata kunci: indeks eritrosit rerata, diabetes melitus tipe 2